A light and electron-microscopic study of microsporogenesis in azolla-microphylla - Herd, Y.R.; Cutter, E.G.; Watanabe, I. (Cambridge University Press, 1985)
SynopsisMicrosporogenesis in cultured material of Azolla microphylla was studied with the light and transmission electron microscopes. The first formed sporangium, a megasporangium, aborts and several microsporangia develop below. Initially, a single sporogenous cell is present, surrounded by a single layered tapetum and the microsporangial wall. Subsequently, several sporogenous cells are connected by plasmodesmata. The microspore mother cells are less densely cytoplasmic than the tapetal cells. Callose-like material is deposited around the microspore mother cells, but disappears before meiosis. The tetrads of microspores contain well defined organelles but less dense cytoplasm than the surrounding periplasmodium. Electron dense material deposited on the plasma membrane of the microspores eventually forms the endospore. The unornamented exospore develops by continued deposition of electron dense material. Degeneration of the periplasmodium gives rise to membranous material which appears to form a template for the massulae.